2011
DOI: 10.1016/j.molcel.2011.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between HDAC3 and WDR5 Is Essential for Hypoxia-Induced Epithelial-Mesenchymal Transition

Abstract: Epithelial-mesenchymal transition (EMT) is important for organ development, metastasis, cancer stemness, and organ fibrosis. Molecular mechanisms to coordinately regulate hypoxia-induced EMT remain elusive. Here, we show that HIF-1α-induced histone deacetylase 3 (hdac3) is essential for hypoxia-induced EMT and metastatic phenotypes. Change of specific chromatin states is associated with hypoxia-induced EMT. Under hypoxia, HDAC3 interacts with hypoxia-induced WDR5, recruits the histone methyltransferase (HMT) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
236
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 242 publications
(252 citation statements)
references
References 50 publications
15
236
0
1
Order By: Relevance
“…Previous analyses of the migratory transcriptome have tended to rely on microarrays of cell populations, such as populations of border cells in Drosophila (7,8) and heart cells in Ciona (9). More recently, RNA-seq (10) and functional genomics (11) have been used to identify mammalian genes involved in the transition to invasive mesenchymal cell types. In C. elegans, it should be possible to combine such RNA-seq with single-cell analysis to achieve a comprehensive inventory of genes involved in migration, with precise temporal resolution.…”
mentioning
confidence: 99%
“…Previous analyses of the migratory transcriptome have tended to rely on microarrays of cell populations, such as populations of border cells in Drosophila (7,8) and heart cells in Ciona (9). More recently, RNA-seq (10) and functional genomics (11) have been used to identify mammalian genes involved in the transition to invasive mesenchymal cell types. In C. elegans, it should be possible to combine such RNA-seq with single-cell analysis to achieve a comprehensive inventory of genes involved in migration, with precise temporal resolution.…”
mentioning
confidence: 99%
“…We found that HDAC3Y298F (an HDAC3 mutant devoid of deacetylase activity; ref. 45) reinforced, as HDAC3 WT, the WWOX-BCL9-2 association, and that the general inhibitor of histone deacetalyses TSA did not impair the ability of HDAC3 to promote WWOX-BCL9-2 interaction in 293 cells (Fig. 7A and data not shown).…”
Section: Hdac3 Promotes the Wwox-bcl9-2 Association Independently Of mentioning
confidence: 75%
“…Cells were cross-linked 46 with 2% formaldehyde for 10 min and stopped by adding glycine to a final concentration of 0.125 M. Fixed cells were washed twice with Tris-buffered saline (TBS) (20 mM Tris, pH 7.5, 150 mM NaCl) and collected in 5 ml of SDS buffer (50 mM Tris, pH 8.0, 0.5% SDS, 100 mM NaCl, 5 mM EDTA and protease inhibitors). Cells were pelleted by centrifugation and suspended in 2 ml of immunoprecipitation (IP) buffer (100 mM Tris, pH 8.6, 0.3% SDS, 1.7% Triton X-100 and 5 mM EDTA).…”
Section: Methodsmentioning
confidence: 99%
“…The sample processing and 11,24,46 IHC procedure for determining the immunoreactivity of Twist1, Jagged1 and KLF4 were described as the following. The paraffin-embedded tissue specimens were de-paraffinized in xylene, rehydrated through 100, 90, 70, 50% ethanol and rinsed in PBS buffer.…”
Section: Oecm1-mentioning
confidence: 99%